Teoretyczne aspekty bezrobocia technologicznego - Węgrzyn, Grażyna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The currently most controversial issue is the unemployment accompanying economic growth. Generally, economic growth is accompanied by economic development, leading to modernization of economy, changes in its structure and improved living standards. New areas of manufacturing, services, and modem technologies emerge alongside. However, the technological changes in economy give rise to significant and permanent change in the structure of labour demand. This leads to technological unemployment. The objective of this article is to present the concept, causess, and scope of technological unemployment in the modern economy. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (16); 2008; nr 1193, s. 350-359